From Super-Enhancer Non-coding RNA to Immune Checkpoint: Frameworks to Functions - Wu, Manqing; Shen, Jun (Frontiers in Oncology, 2019)
Super-enhancers (SEs) are clusters of enhancers that play a key role in regulating genes that determine cell identity. Enhancer RNAs (eRNAs) are non-coding RNAs transcribed from enhancers that function to promote the enhancer’s functions via multiple mechanisms, such as recruiting transcription factors to specific enhancers, promoting enhancer-promoter looping, directing chromatin accessibility, interacting with RNA polymerase II and facilitating histone acetylation. Understanding how super-enhancer RNAs (seRNAs) contribute to specific gene regulation has thus become an area of active interest. Immune checkpoint deregulation is one of the key characteristics of tumors and autoimmune diseases, and is also closely related to cell identity. Recent studies revealed a potential pathway for seRNA’s involvement in regulating the expression of immune checkpoints. The present study reviews the current knowledge of eRNA function, immune checkpoint blockage mechanism, and its effect. In addition, for the first time, we explore the direct and indirect roles of seRNAs in regulating immune checkpoint expression in cancer and autoimmune diseases.